Analisis Pengaruh Variabel Makroekonomi, Harga Komoditas Dunia, Dow Jones, dan Shanghai Stock Exchange Terhadap Indeks Harga Saham Gabungan Periode 2014-2018 - TETY YULIANTI, MELINDA; PURWOHANDOKO, (Jurnal Ilmu Manajemen (JIM), 2019)
This research aims to analyze the effect of macroeconomic variables, world commodity price, and global stock index on Jakarta Composite Index. The macroeconomics variables include the inflation, exchange rate, SBI rate, gross domestic product, and money supply. While the world commodity prices include oil prices and gold prices. Global stock index include Dow Jones and Shanghai Stock Exchange. The sampling in this study uses a saturated sampling method (census) because it uses monthly JCI data during the 2014-2018 period, so the sample of this study were 60. The data analysis technique is multiple linear regression. The outputs indicate that exchange rate have a negative effect on Jakarta Composite Index. Meanwhile, SBI rate, gross domestic product, money supply, oil prices, gold prices, Dow Jones, and Shanghai Stock Exchange have no significant effect on Jakarta Composite Index. But, all independent variables have simultaneously effect on Jakarta Composite Index. The research variable was only able to explain 22.8% on JCI, while the remaining 77.2% was explained by the other variables outside of this research model. Keywords: Commodities; DJIA; JCI; Macroeconomics; SSE.